Post-Modernism and the Emergence of Alternate History - Atqo Akmal (Tarikhuna: Journal of History and History Education, 2024)
The emergence of post-modernism in the mid-20th century marked a seismic shift in historical knowledge, challenging long-held assumptions about the relationship between language, truth, and reality. This paper explores the profound impact of post-modernism on the discipline of history, focusing on its influence on the concept of alternate history. Post-modernist thought contends that language constructs our understanding of the world rather than merely representing reality, leading to the recognition that there is no single, objective truth in history. The paper delves into the critiques and alternative frameworks notable historians propose within this post-modernist framework. It begins by examining Alun Munslow's concept of "deconstructing history," which encourages historians to critically analyze historical narratives and acknowledge the subjectivity inherent in interpretation. Keith Jenkins's "own-sakism" is introduced as a response to the post-modernist critique of historical objectivity, advocating for acknowledging and embracing historians' subjectivity. The paper also explores Hayden White's "metahistory," which critiques the narrative structure of history and invites historians to be more self-conscious about narrative choices. It concludes by highlighting the enduring legacy of post-modernism in history, emphasizing the importance of reflexivity, transparency, and critical self-examination in the pursuit of historical knowledge. The paper contends that post-modernism has not only challenged historical objectivity but has also opened up new possibilities for a more inclusive and diverse historiography.